Cunoștințele teoretice și evitarea interpretărilor defectuoase, contrare Constituției [Articol] - Aramă, Elena (CEP USM, 2020)
In this article it is reconsidered how the ignorance of the main teoretical concepts with their philosophical-legal meaning is one of the factors that generated political crisis in the Republic of Moldova in the summer 2019.
THEORITICAL KNOWLEDGE AND AVOIDANCE MISINTERPRETATIONS, CONTRARY TO THE CONSTITUTION
Keywords: theory of law; legal philosophy; political crisis